Amorphous lactose crystallisation kinetics. (May 2016) - Clark, Z.; Paterson, A.H.J.; Joe, R.; Mcleod, J.S.
Abstract: Amorphous lactose crystallisation kinetics were investigated at different relative humidity and temperature combinations. Amorphous lactose was equilibrated to a water activity of 33%, then placed in sealed pans with a saturated magnesium chloride solution to maintain a constant relative humidity (33%). The temperature was raised to 10–40 °C above the glass transition temperature (Tg ). The degree of crystallisation was measured using isothermal microcalorimetry. Crystallisation was shown to be an all-or-nothing event, such that direct measurement of the kinetics was not possible. This was not expected from the Avrami model. The rapid crystallisation could be an autocatalytic effect, as moisture is released during crystallisation, or a showering event as seen in highly supersaturated lactose solutions. Experiments using a blend of crystalline and amorphous lactose, produced by spray drying a lactose crystal slurry, showed crystallisation occurring at lower Tg conditions than was required for the crystallisation of 100% amorphous lactose.